Aplikace quaternionů v kinematice robotu - Doctor, Diana (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
This thesis deals with the usefulness of the application of quaternions in representing robot kinematics. It begins by showing the relationship of quaternions to the more commonly-known complex numbers and how it can represent rotations in three-dimensions. Then, the dual quaternions are introduced to represent both the three-dimensional rotation and translation. It will then be used to derive the forward and inverse kinematics, particularly, for the Universal Robot UR3 which is a 6-DOF robotic arm. Lastly, an actual application of dual quaternions in robot programming will be demonstrated

This thesis deals with the usefulness of the application of quaternions in representing robot kinematics. It begins by showing the relationship of quaternions to the more commonly-known complex numbers and how it can represent rotations in three-dimensions. Then, the dual quaternions are introduced to represent both the three-dimensional rotation and translation. It will then be used to derive the forward and inverse kinematics, particularly, for the Universal Robot UR3 which is a 6-DOF robotic arm. Lastly, an actual application of dual quaternions in robot programming will be demonstrated
Applications of Quaternions in Robot Kinematics
Keywords: quaternions; dual quaternions; robotics; universal robot; UR3; forward kinematics; inverse kinematics; three-dimensional rotations; quaternions; dual quaternions; robotics; universal robot; UR3; forward kinematics; inverse kinematics; three-dimensional rotations